Quasi-valuation maps based on positive implicative ideals in BCK-algebras - Young Bae Jun; Kyoung Ja Lee; Seok Zun Song (Algebra and Discrete Mathematics, 2018)
The notion of PI-quasi-valuation maps of a BCK-algebra is introduced, and related properties are investigated. The relationship between an I-quasi-valuation map and a PI-quasivaluation map is examined. Conditions for an I-quasi-valuation map to be a PI-quasi-valuation map are provided, and conditions for a real-valued function on a BCK-algebra to be a quasi-valuation map based on a positive implicative ideal are founded. The extension property for a PI-quasi-valuation map is established.